BIBLIOMETRIC INSIGHTS INTO ASSESSMENT PRACTICES IN THE MERDEKA CURRICULUM: IDENTIFYING OPPORTUNITIES FOR NEW ASSESSMENT DEVELOPMENT - Hadiastriani, Yasmine; Djarot, Prasetyorini; Chemistry, Valerie Indiana (Universitas Pakuan, 2024)
The Merdeka Curriculum in Indonesia represents a transformative educational reform emphasizing holistic student development. However, conventional assessment methods have proven inadequate in comprehensively evaluating these desired learning outcomes. This study employs bibliometric analysis to systematically examine the research landscape surrounding the multiple assessment in the context of Merdeka Curriculum. Through data mining from the Google Scholar database spanning 2018 to 2023, the findings reveal a significant gap between the substantial academic interest in multiple assessments, as evidenced by 2,727 citations from 660 publications, and the limited number of studies (92 articles with 187 citations) explicitly focused on developing new assessment instruments. Keyword analysis further highlighted the under representation of terms like